Adaptive detection for resolvable multipath signal under heterogeneous clutter. Issue 1 (4th October 2022) - Cao, Chun; Fan, Chongyi; Du, Huagui; Wang, Jian; Huang, Xiaotao
Abstract: In the urban environment, the radar is easily affected by multipath (MP) returns. The problem of detecting point‐like targets in the urban environment with the existence of resolvable MP returns under the background of heterogeneous clutter is addressed. Two adaptive detectors have been devised with a combination of prior information on the environment and echoes of target. The detectors can use the MP echoes in all MP prediction range cells for detection or in some available paths for signal detection by the available path selection algorithm that eliminates the weak signal propagation paths. Remarkably, the proposed decision schemes exhibit the desirable constant false alarm rate property with respect to the unknown parameters of the heterogeneous interference. The performance assessment, conducted on simulated data in terms of detection probability also in comparison with conventional solutions, highlights the effectiveness of the MP exploitation, while the MP signal is strong and shows the detection performance enhancement potential.